2020
DOI: 10.1371/journal.pone.0239179
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of patient safety health policies: Delphi survey using patient safety experts in Japan

Abstract: Various patient safety interventions have been implemented since the late 1990s, but their evaluation has been lacking. To obtain basic information for prioritizing patient safety interventions, this study aimed to extract high-priority interventions in Japan and to identify the factors that influence the setting of priority. Six perspectives (contribution, dissemination, impact, cost, urgency, and priority) on 42 patient safety interventions classified into 3 levels (system, organizational, and clinical) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…All these interventions had low scores for past contribution and current dissemination, as evaluated by safety managers. Our previous study on Japanese patient safety experts suggested that experts are likely to evaluate the priority of patient safety interventions with the expected impact in the future [ 20 ]. These results suggest that safety managers were likely to evaluate the priority of patient safety interventions in terms of which interventions were effective and important in the past, while experts were likely to evaluate what was lacking now for further improvement in patient safety.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All these interventions had low scores for past contribution and current dissemination, as evaluated by safety managers. Our previous study on Japanese patient safety experts suggested that experts are likely to evaluate the priority of patient safety interventions with the expected impact in the future [ 20 ]. These results suggest that safety managers were likely to evaluate the priority of patient safety interventions in terms of which interventions were effective and important in the past, while experts were likely to evaluate what was lacking now for further improvement in patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a secondary data analysis of two surveys: the Delphi survey for Japanese experts [ 20 ] and a nationwide questionnaire survey for patient safety managers in hospitals [ 23 ]. Parts of both questionnaire items used in this study were shown in S1 and S2 Tables.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations